Representations of Ideology and Multicultural Values in Imported English Textbooks and their Impacts on Indonesian Students’ Characters - Sinaga, Tuntun (Journal of Research in Social Science and Humanities, 2024)
Studies on ideology and multicultural values in English textbooks have been carried out in the last decades. However, studies on foreign-published or imported textbooks used in Indonesian schools have been still scarce in literature. The current research was aimed at investigating the representation of ideology and multicultural values in the English textbooks used in Indonesian schools. This method employed in the study was a critical discourse analysis (CDA) on learning materials contained in English textbooks used in Indonesian secondary schools. The results revealed that the representation of ideology and multicultural values were identifiable through various forms of the culture, culinary topics, tourist attractions, youth lifestyles, flora and fauna, modern life achievement as well as interpersonal interactions. The current research findings offer different perspectives in developing English teaching materials in adjusting the balance of ideological and multicultural stances in shaping the learners’ characters.